Grabbing the plantain market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Plantain for export from the Eastern Caribbean: Production and marketing manual G C Robin, H C Chamberlain & D N Crucefix. CARDI/CTA. 2000. 26pp. ISBN 976 617 006 1 CTA number 981. 5 credit points